Overcurrent protection of AC microgrids using mixed characteristic curves of relays. (March 2019) - Alam, Mahamad Nabab
Abstract: Protection of AC microgrids with islanded and grid-connected modes of operation is a major challenge as fault currents change drastically in the transition from one mode to the other. In this paper, optimum settings of directional overcurrent relays (DOCRs) considering different characteristic curves for the protection of AC microgrids with islanded and grid-connected modes of operation is presented. In this work, all the relays are considered to be associated with three variables which are time multiplier-setting (TMS), plug-setting (PS), and curve-setting (CS) to obtain their correct operating times. Here, TMS, PS, and CS are associated with time scaling, pickup current value and characteristic curve selection, respectively, of a DOCR. The proposed protection coordination problem has been formulated as a mixed-integer nonlinear programming problem and solved using the genetic algorithm in MATLAB environment. The effectiveness and suitability of the proposed approach have been demonstrated on 7 and 18 bus microgrids.